Spine surgery and readmission: Risk factors in lumbar corpectomy patients - Julius Gerstmeyer, MD; Anna Gorbacheva; August Avantaggio; Clifford Pierre, MD; Emre Yilmaz, MD; Thomas A. Schildhauer, MD; Amir Abdul-Jabbar, MD; Rod J Oskouian, MD; Jens R Chapman, MD (North American Spine Society Journal)
Background: A corpectomy of the lumbar spine is a widely performed surgical procedure with numerous indications. Previous research predominantly focused on various surgical techniques and their outcomes, lacking a general and comprehensive analysis of factors affecting this procedure. With this study, we aimed to assess the all-cause 90-day readmission rate and identify risk factors for adverse events following a lumbar corpectomy. Methods: Utilizing the 2020 Nationwide Readmissions Database adults (>18 years) were selected by ICD-10 procedure category codes for lumbar corpectomy. Patients with adult deformity or degenerative conditions were excluded due to coding inconsistencies. Demographic information and clinical data, including comorbidities, was extracted. Patients were categorized by their readmission status. The primary outcome was readmission, with multivariable logistic regression analysis used to identify independent risk factors. Results: A total of 3,238 patients were included, with 20.8% readmitted. The readmission group was significantly older and had higher comorbidity burdens. Malignancy had the greatest odds of readmission (OR 3.172, p=.002), with spondylodiscitis also showing significant association (OR 2.177, p=.030). Fractures were significantly more frequent in the single admission group and not associated with readmission (OR 1.235, p=.551). Medical comorbidities differed significantly between the groups with a variety of them being identified as risk factors. Conclusions: We established an all-cause 90-day readmission rate of 20.8%, which is in range of other procedures in spine surgery but underscores the severity of lumbar corpectomy. Underlying pathologies have a greater impact on the readmission rate compared to medical comorbidities. These findings highlight the importance of preoperative patient selection, especially when performing more invasive procedures. However, the study's limitations may limit the generalizability of the findings.